Kansas Swine Improvement Association Testing Station - Koch, B.A.; Moyer, W.A. (Kansas Agricultural Experiment Station, 2011)
The boar testing program was changed to a slaughter-pig testing program a year ago. The testing station committee of the Association made the change because of the difficulty in identifying carriers of infectious atrophic rhinitis. In the group of boars tested during the winter of 1961-62, one of the better performing boars showed positive symptoms of infectious atrophic rhinitis soon after he sold. Yet he had shown no symptoms of infection while on test.
Keywords: Swine; Performance; Infectious atrophic rhinitis